THE EFFECTS OF WATER ADDITION AND STEAMING DURATION ON STARCH COMPOSITION OF WHEAT POLLARD - Cahya Setya Utama; Bambang Sulistiyanto; Sri Kismiati (Reaktor, 2017)
Abstract The objective of the study was to determine the effects of water addition and steaming duration on starch composition of wheat pollard including starch, amylose, amylopectin and starch resistant. Water was added towheat pollard (0, 30 and 60%) and autoclaved at 121°C (15 and 30 min) afterward. The pollard then was oven-dry at 70°C. The study used a complete randomized design of  3x2 factorial with 3 replications. The addition of water and steaming duration showed a very significant (p<0.001) impact on the amylose and starch resistant parameters but not the starch and amylopectin. The addition of water increased the starch content from 38.71+0.10%. The starch content of a 15-min autoclave was higher (44.54+11.34%) than that of a 30-min (43.43+11.16%).  The amylose levels decreased with addition of water and duration of autoclave. The amylose decrease from 5.23+0.10%  to 4.03+0.32%. Addition of water increased the amylopectin level from 33.50+0.10 to 52.90+0.70% while the amylopectin level was heated at 15 minutes (39.79+11.76%) and decreased to 39.20 + 11.44% after treatment with steam for 30 minutes. Addition of water increased the starch resistant level from 8.75+1.06% to 15.40+ 1.51% while heating for15 minutes had the highest starch resistant of 16.65+0.04% compare to the longer steaming deration. This result concluded that the addition of water and the duration of steam greatly affects the content of starch, amylose, amylopectin and starch resistant of the wheat pollard. The best results of this study was the addition of 30% moisture content with a steam duration of 15 minutes which results in the highest starch resistant of 16.65+ 0.04%. Keywords: wheat pollard; steam; moisture content; starch; amylose; starch resistant